Modified high-flow nasal cannula for children with respiratory distress - Sarocha Itdhiamornkulchai; Aroonwan Preutthipan; Jarin Vaewpanich; Nattachai Anantasit (The Korean Pediatric Society, 2022)
Background High-flow nasal cannula (HFNC) is a noninvasive respiratory support that provides the optimum flow of an air-oxygen mixture. Several studies demonstrated its usefulness and good safety profile for treating pediatric respiratory distress patients. However, the cost of the commercial HFNC is high; therefore, the modified high-flow nasal cannula was developed. Purpose This study aimed to compare the effectiveness, safety, and nurses' satisfaction of the modified system versus the standard commercial HFNC. Methods This prospective comparative study was performed in a tertiary care hospital. We recruited children aged 1 month to 5 years who developed acute respiratory distress and were admitted to the pediatric intensive care unit. Patients were assigned to 2 groups (modified vs. commercial). The effectiveness and safety assessments included vital signs, respiratory scores, intubation rate, adverse events, and nurses' satisfaction. Results A total of 74 patients were treated with HFNC. Thirty-nine patients were assigned to the modified group, while the remaining 35 patients were in the commercial group. Intubation rate and adverse events did not differ significantly between the 2 groups. However, the commercial group had higher nurses' satisfaction scores than the modified group. Conclusion Our findings suggest that our low-cost modified HFNC could be a useful respiratory support option for younger children with acute respiratory distress, especially in hospital settings with financial constraints.